2017
DOI: 10.1002/ajp.22692
|View full text |Cite
|
Sign up to set email alerts
|

Using video and theater to increase knowledge and change attitudes—Why are gorillas important to the world and to Congo?

Abstract: Applying environmental education in primate range countries is an important long-term activity to stimulate pro-conservation behavior. Within captive settings, mega-charismatic species, such as great apes are often used to increase knowledge and positively influence attitudes of visitors. Here, we evaluate the effectiveness of a short-term video and theater program developed for a Western audience and adapted to rural people living in two villages around Nouabalé-Ndoki National Park, Republic of Congo. We asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 47 publications
(86 reference statements)
2
25
0
Order By: Relevance
“…Kuhar et al () have emphasized the importance of evaluation in conservation education programs if we are to understand which activities contribute to conservation success. The most commonly used assessment method is the questionnaire or survey (Breuer, Mavinga, Evans & Lukas, ; Kuhar et al, ; Rakotomamonjy et al, ). And, although Dolins et al () reported that comic and storybooks are useful methods for conveying conservation and ecological knowledge, they indicated that, during the evaluation, “many questions were not answered because children required greater thought and the ability to write” (Dolins et al, : 401).…”
Section: Introductionmentioning
confidence: 99%
“…Kuhar et al () have emphasized the importance of evaluation in conservation education programs if we are to understand which activities contribute to conservation success. The most commonly used assessment method is the questionnaire or survey (Breuer, Mavinga, Evans & Lukas, ; Kuhar et al, ; Rakotomamonjy et al, ). And, although Dolins et al () reported that comic and storybooks are useful methods for conveying conservation and ecological knowledge, they indicated that, during the evaluation, “many questions were not answered because children required greater thought and the ability to write” (Dolins et al, : 401).…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, it is important to test different educational techniques to include cultural factors, gender diversity, and different learning styles. For instance, applying educational techniques (including evaluations) that work for an audience from a high-income country might not necessarily lead to the expected change in a low-income country [4]. In Mexico, ESD is poorly implemented in the school curricula, and arts education is rarely taught [25].…”
Section: Technique Usedmentioning
confidence: 99%
“…Our study shows that considering multiple intelligences and senses can improve the effectiveness of CE programs. Not only the intervention, but also the evaluation should also be inclusive to all learners and indigenous cultures, since in primate CE assessment is commonly done through questionnaires [4,29,60]. Drawings have been an excellent tool for evaluating the effectiveness of CE programs, as well as an artistic approach that evaluated the children's knowledge on black howler monkeys.…”
Section: Technique Usedmentioning
confidence: 99%
See 2 more Smart Citations